Social learning processes of HIV/AIDS women caregivers on their use of traditional foods and medicinal plants : the case of Raphael Centre and Keiskamma Art and Health Centre communities of practice, Eastern Cape Province, South Africa - Shonhai, Venencia F (Rhodes University, Faculty of Education, Department of Education, 2009)
The scale of people being infected by HIV/AIDS (Human Immunodeficiency Virus /Acquired Immune Deficiency Syndrome) has meant that the family and the community have had to become involved in caring for the sick (Van Dyk, 2005). This has inevitably led to the emergence of informal caregivers in the form of family members caring for their relatives (Kipp, Nkosi, Laing & Jhangri, 2006). The research investigated the social learning of women caregivers looking after people living with HIV/AIDS, with emphasis on caregiving practices related to how they use traditional foods and medicinal plants. The research was undertaken in Grahamstown at the Raphael Centre and in Hamburg at Keiskkamma Health Centre and Art Project, Eastern Cape, South Africa. Data was collected using interviews, focus group discussions and diaries written by participants. The data was analyzed in two phases: the first phase involved reading the interview transcripts and collating the responses into analytical memos that were captured into broad categories, while the second phase made use of the community of practice analytical framework to further analyze the data to get better understanding of the social learning processes. This study reveals that participating in a community of practice like Raphael Centre and Keiskamma Health Centre enables caregivers to learn about caregiving. It also reveals that within these communities of practice there are varied learning processes that take place, such as observational and collaborative learning. The research also revealed that caregivers learn from the communities from which they come, for example caregivers learn about traditional food and medicinal plants which they use from their family members, friends, other caregivers as well as non governmental organizations. The research found that caregivers are influenced in their learning and practices by a number of factors which include their own experiences, ambivalent messages from different stakeholders concerned with fighting HIV/AIDS and exposure to new information. The research recommends that diverse learning processes in a community of practice and outside a community of practice should be encouraged and strengthened. It also recommends that HIV/AIDS caregiving options should be strengthened by drawing on experience and knowledge of caregivers. Caregivers should be encouraged to be selfsustaining to improve their caregiving practices. Stakeholders in the field of HIV/AIDS should be alert to and address ambivalence on use of medicinal plants. Existing programmes that enable women to learn about new information on HIV/AIDS should be strengthened.
Keywords: Keiskamma Art Project (South Africa); Women caregivers -- South Africa -- Eastern Cape; HIV infections -- Study and teaching -- South Africa; AIDS (Disease) -- Study and teaching -- South Africa; HIV-positive persons -- Care -- South Africa -- Eastern Cape; Medicinal plants -- South Africa; Natural foods -- South Africa